Insights into the mechanisms of arsenic-selenium interactions and the associated toxicity in plants, animals, and humans: A critical review. Issue 7 (3rd April 2021) - Ali, Waqar; Zhang, Hua; Junaid, Muhammad; Mao, Kang; Xu, Nan; Chang, Chuanyu; Rasool, Atta; Wajahat Aslam, Muhammad; Ali, Jamshed; Yang, Zhugen
Abstract: This review highlights arsenic (As) and selenium (Se) sources in the environment, their uptake in the soil-plant system, interactions between these metals and the associated toxicity in major biological compartments, which may assist in addressing the hazardous impacts associated with As and Se contamination. The interaction between As and Se is a critical factor for a detailed systematic understanding of the transportation, environmental fate, and associated toxicological effects of these metalloids in plants, animals, and humans. Arsenic and Se induce cytotoxicity and genotoxicity through the generation of reactive oxygen species (ROS). Compared to arsenite (As III ), methylated arsenicals, including methylarsonous acid (MAs III ) and dimethylarsinous acids (DMAs III ), exhibit more cytotoxic and genotoxic potential to inhibit more potent enzymes and activate the protein AP˗1, which is a critical marker of genetic stability. Methylated As III and its associated metabolites are well-known potential carcinogens that induce toxicity by blocking Se metabolism pathway. The imbalance of Se compounds can lead to the generation of ROS, which can inhibit or decrease genomic stability. The As and Se nexus also affect cellular signaling through activation of transcription factors such as NFκB and AP-1. Graphical Abstract: UF0001